Randomized, Double‐Blind, Dose‐Escalation Trial of Triptorelin for Ovary Protection in Childhood‐Onset Systemic Lupus Erythematosus. Issue 5 (May 2015) - Brunner, Hermine I.; Silva, Clovis A.; Reiff, Andreas; Higgins, Gloria C.; Imundo, Lisa; Williams, Calvin B.; Wallace, Carol A.; Aikawa, Nadia E.; Nelson, Shannen; Klein‐Gitelman, Marisa S.; Rose, Susan R.
<x xml:space="preserve">Abstract</x> Objective To determine the dose of triptorelin that is sufficient to maintain complete ovarian suppression in female patients with childhood‐onset systemic lupus erythematosus (SLE) who require cyclophosphamide therapy, to determine the length of time needed to achieve ovarian suppression after initiation of triptorelin treatment, and to investigate the safety of triptorelin. Methods In this randomized, double‐blind, placebo‐controlled, dose‐escalation study, female patients ages <21 years were randomized 4:1 to receive triptorelin (n = 25) or placebo (n = 6). The starting doses of triptorelin were 25, 50, 75, and 100 μg/kg, and the dose was escalated until complete ovarian suppression was maintained. The primary outcome was the weight‐adjusted dose of triptorelin that provided complete ovarian suppression in at least 90% of the patients, as determined by gonadotropin‐releasing hormone agonist stimulation testing. The secondary outcome was the period of time required to achieve ovarian suppression, as measured by unstimulated follicle‐stimulating hormone and luteinizing hormone levels after the initiation of triptorelin treatment. Results Treatment with triptorelin at a weight‐adjusted dose of 120 μg/kg body weight provided sustained complete ovarian suppression in 90% of the patients. After administration of the initial dose of triptorelin, 22 days were required to achieve complete ovarian suppression. The rates of adverse events (AEs) and serious adverse events (SAEs) per 100 patient‐months of followup were not higher in the triptorelin group compared with the placebo group (for AEs, 189 versus 362; for SAEs, 2.1 versus 8.5). Conclusion High doses of triptorelin are needed to achieve and maintain complete ovarian suppression, but such doses appear to be well tolerated in adolescent female patients with childhood‐onset SLE. Our data suggest that a lag time of 22 days after initiation of triptorelin treatment is required before cyclophosphamide therapy is started or continued.